PENGARUH KOMPETENSI, SISTEM PENGENDALIAN INTERNAL DAN MORALITAS APARATUR TERHADAP POTENSI TERJADINYA KECURANGAN LAPORAN KEUANGAN DALAM PENGELOLAAN KEUANGAN DESA - Wardani, Rizka Maisti; Nasution, M. Irsan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to determine the effect of competence, internal control system, and morality of the apparatus on the potential for fraudulent financial reporting in village financial management in Batang Serangan District, Langkat Regency. The dependent variable in this study is the potential for fraudulent village financial reporting (Y), while the independent variables include competence, internal control system, and morality of the apparatus (X). The type of research is quantitative research. The study population includes all village apparatus and members of the Village Consultative Body (BPD) in Batang Serangan District, Langkat Regency. The sampling technique used the purposive sampling method, resulting in 56 respondents as research samples. Data were collected using a questionnaire and analyzed using multiple linear regression techniques to test the hypothesis. The results showed that the variables of competence and morality of the apparatus had a significant effect on the potential for fraudulent financial reporting in village financial management. However, the internal control system variable did not show a significant effect on the potential for fraudulent financial reporting.